2021
DOI: 10.22178/pos.76-11
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Green Building Features in the Medium-Income Residential Market of Makurdi, Nigeria

Abstract: Investigating willingness to pay for green buildings in Nigeria and other developing nations is an urgent need since the world is advocating sustainable development, which the building industry must adopt while attempting to satisfy housing needs that are yet to be met in most developing countries. Recognizing that medium-income earners are victims of housing deficit who can afford housing to a reasonable extent in Nigeria, this paper aimed to investigate medium-income householders' willingness to pay for a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It can also be inferred that level of education can be attributed to either a high or low level of awareness of green building features. [20,34], found that educational background affects level of awareness and factors with a high degree of influence on users' preference for green features in residential buildings are the educational factor and the income factor. A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also be inferred that level of education can be attributed to either a high or low level of awareness of green building features. [20,34], found that educational background affects level of awareness and factors with a high degree of influence on users' preference for green features in residential buildings are the educational factor and the income factor. A.…”
Section: Resultsmentioning
confidence: 99%
“…The finding shows that 23% of residents were aware of green buildings, and 77% of residents in the high-density area were not aware of green building features. The reasons for this can be attributed to the low level of literacy in this zone as established by [20,32] that a low level of awareness of green building features can be attributed to low educational factors and level of exposure. In the medium density, 39.3% were aware, while 60.7% were not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upfront cost of building green is amongst the most cited inhibitors of green building adoption (Dwaikat & Ali, 2016;Takuh, Adeyemi, et al, 2021) across the extensively studied area of green building adoption drivers and inhibitors globally (Wuni et al, 2019). In Ghana, previous studies have found barriers such as lack of government support , lack of demand (Djokoto et al, 2014), and low sensitization (Guribie et al, 2021) as the most significant hindrances to green building adoption.…”
Section: Willingness To Pay For Green Buildingsmentioning
confidence: 99%
“…There is however ample evidence of willingness to pay for green buildings from other countries. In Nigeria, Takuh, Adeyemi, et al (2021) found mediumincome earners willing to pay a 3.3% premium for green homes. In Indonesia, Njo et al (2021) found 39.7% of respondents willing to pay a 6-15% premium, and 38.53% willing to pay a 5% premium.…”
Section: Willingness To Pay For Green Buildingsmentioning
confidence: 99%